Assessing the Willingness of Indonesian and Malaysian University Students to Receive the Covid-19 Vaccine: Implications for Public Health Sustainability - Hendra Lukito; Harif Amali Rivai; Nor Azilah Husin; Norfadzilah Abdul Razak (Universitas Pasundan, 2024)
This study investigates the factors influencing university students' willingness to receive Covid-19 vaccinations in Indonesia and Malaysia, with a focus on sustainability. Vaccination is essential for pandemic management and contributes to social and economic sustainability by reducing healthcare burdens and enhancing public health as human capital. However, vaccine hesitancy among young adults remains a concern. This study analyzes four key determinants—trust, attitudes, religiosity, and social media influence—using survey data and Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The findings reveal differences between the two countries: religiosity and social media were not significant for Indonesian students, while social media and trust were insignificant for Malaysian students. These results emphasize the need for culturally tailored vaccination strategies. The study also underscores the role of educational institutions in promoting sustainability through effective vaccination communication. Mass vaccination supports public health, mitigates pandemic-related economic impacts, and fosters a healthier student population, contributing to long-term social and economic resilience. Educational institutions are encouraged to integrate vaccination efforts into their accountability and sustainability reporting frameworks, demonstrating their commitment to social responsibility and sustainable development. This research offers valuable insights for designing targeted, context-specific interventions to enhance vaccination uptake among university students in Southeast Asia.